Potential land microalgae cultivation in Mexico: From food production to biofuels - Lozano-Garcia, D. F.; Cuellar-Bermudez, S. P.; Del Rio-Hinojosa, E.; Betancourt, F.; Aleman-Nava, G. S.; Parra-Saldivar, R.
A geographic information system model was built to identify the areas in Mexico with high potential for microalgae production. The input data was obtained from diverse national and international sources. The model was constructed using multiple criteria for facility siting, including the following land characteristics and resources: land use, topographic slope, temperature, evaporation, solar radiation, vegetation, water and CO2 sources, wastewater treatment plants, rivers and lakes, cities and roads, natural protected areas, historical sites, Ramsar sites, airport locations and geological faults. Various models were constructed by assigning weights according to suitability to the data layers. Suitable areas for microalgae production were identified in up to 26.8 percent of the country, equivalent to 526,672?km2. Specifically, the states of Jalisco, Oaxaca and Veracruz had the largest areas suitable for microalgae cultivation, with a potential production of around 9?million?Tonnes?yr?1 of dry biomass, representing the feasibility of microalgae production in the country.
Keywords: GEOGRAPHIC INFORMATION SYSTEM; BIOMASS; MICROALGAE; OPEN POND; CARBON DIOXIDE; WATER; MEXICO